Infusing Computer Technology: A Novice Teacher User Meets the Challenge with High School ESL Students - Shelia Baldwin (Networks: An Online Journal for Teacher Research, 2001)
This account is a continuing exploration of my integration of computer technology that expanded to include specifically the use of Hyperstudio, Power Point, and the Internet with ESL students in an American Culture Studies class, an ESL I Reading class, and a Reading remediation class.